Optimizing Hemostatic and Antithrombic Therapies: A Comprehensive Stewardship Strategies - Ismail, Rabiyath Riswana; Jayabal, Ramya; Kumar, Raveena Rajesh; Rajan, Redlin Jani (Indian Journal of Pharmacy Practice)
Optimizing hemostatic and antithrombotic therapies in clinical practice requires a robust and systematic approach to ensure patient safety, therapeutic efficacy and adherence to evidence-based guidelines. The tertiary care setting’s appropriate use of hemostatic and antithrombotic drugs is optimized through the deployment of a comprehensive stewardship strategy, as described in this abstract. The stewardship program’s main goal is to reduce bleeding and thrombotic events. To achieve this, the most recent American College of Cardiology/ American Heart Association (ACC/AHA) recommendations for therapeutic optimization are being implemented. Standardized protocol development, ongoing education for healthcare personnel and real-time decision support systems are important elements of the approach. The stewardship team, comprising multidisciplinary experts, conducts regular audits and feedback sessions to monitor adherence to prescribed guidelines and identify areas for improvement. Patient outcomes are assessed through various metrics, including medication adherence, satisfaction, quality of life and cost-effectiveness, using meticulously designed self-administered questionnaires. Preliminary data suggest a significant reduction in adverse events and improved patient outcomes, highlighting the potential of stewardship programs in optimizing anticoagulant and antithrombotic therapy. In order to improve patient safety and results, a more widespread deployment of this descriptive analysis throughout healthcare systems is advocated. It emphasizes the significance of a coordinated, evidence-based approach to the handling of drugs. This review concludes by addressing the complexities of hemostatic and antithrombotic therapies, this stewardship model demonstrates the critical role of interdisciplinary collaboration and continuous quality improvement in modern healthcare.
Keywords: Anticoagulants; Antithrombotic; Education; Multidisciplinary; Stewardship